Assessing the net climate benefits of improved grazing intensity in global rangelands - Robert S. Powell; Steven J. Davis; David G. Encarnation; Johannes Piipponen; Jinfeng Chang; Courtney M. Currier; Karl-Heinz Erb; Samuel Eze; Chaopeng Hong; Pierre Ploton; Shuai Ren; Pete Smith; et al. (Science, 2026)
Improved rangeland grazing could mitigate climate change through carbon dioxide (CO 2 ) sequestration in soils and vegetation. However, altering grazing practices to increase ecosystem carbon storage may also decrease livestock production and/or increase greenhouse gas emissions through the supply chain, such that the net emissions impacts remain unclear. Here, we assess the global net mitigation potential of improving grazing intensity by quantifying potential CO 2 sequestration alongside systems-level impacts of plant productivity changes, livestock emissions, feed requirements, and production constraints. Improving grazing intensity in global rangelands could sequester 2.2 ± 0.43 gigatons of carbon dioxide equivalent (Gt/CO 2 eq) per year in the near term, but maintaining livestock production through supplemental feeding would reduce net mitigation by 2 to 31% (to 1.8 ± 0.45 GT/CO 2 eq per year). Our results suggest that neglecting systems-level emissions impacts may substantially overestimate the global climate benefits of improved grazing.